The influence of anatomical location on the accuracy of tonsillolith diagnosis on panoramic radiographs - Matheus Herreira-Ferreira; Gustavo Nascimento de Souza-Pinto; Fernanda Chiguti Yamashita; Fernanda Silvestre; Breno Gabriel da Silva; Elen de Souza Tolentino; Mariliani Chicarelli; Lilian Cristina Vessoni Iwaki (Universidade Estadual de Maringá, 2024)
This study aimed to analyze the influence of anatomical location regarding the accuracy of the diagnosis of tonsilloliths on panoramic radiographs.Of 2022 digital panoramic radiographs analyzed, 181 presented tonsilloliths. The images were reevaluated and classified according to six anatomical regions. The findings were related to gender and age. Variables were tested using the Chi-square test. The Receiver Operational Characteristic Curve (ROC) evaluated the performance in identifying the region that presented tonsilloliths. The Kappa test was used for intra and inter-examiner agreement (p < 0.05). Of the 181 patients (8.95%) with tonsilloliths, 104 (57.46%) were male (p < 0.05). The most prevalent age group was ≥49 years (p < 0.05). Unilateral/bilateral ratio was 2.5:1. The Kappa values for intra and inter-examiner showed substantial to almost perfect scores. The most common location of the tonsilloliths was the mandible ramus, superimposed on the soft palate (p < 0.05), presenting the largest area under the curve (AUC) and the greatest accuracy (AUC= 0.70; 0.66) as well. Likewise, this location and the location postero-inferior to the mandible angle showed greater sensitivity and specificity. In the panoramic radiographs image, tonsilloliths are most often superimposed on the mandible ramus, with greater accuracy and sensitivity for its detection.